Carotid Body Paraganglioma A Rare Disease - Kekre, Dr. Meenakshi; Kekre, Dr. Anant (International Journal of Innovative Research in Medical Science, 2018)
This study was aimed to evaluate the management of carotid body paraganglioma, the best approach to have the diagnosis and to classify them on the basis of Shamblin’s classification. A series of 5 cases reporting to the department in 4 years was taken and retrospectively analysed. One of them was having large bilateral pulsatile mass with bruit and few neurological symptoms like hoarseness of voice. One of the patient was diagnosed during routine investigation as she was having small nodular swelling right side of neck but otherwise asymptomatic. FNAC was diagnostic which was advised as in any other nodal mass. Rest three cases were also in type II but had only localized symptoms. All cases were investigated with CT scan and colour Doppler studies. Three cases were operated, one was referred and another one being asymptomatic was not ready for any surgical intervention. The outcome was evaluated. There were no major complications or recurrences seen.